Pós-condicionamento com curcuma e eletroacupuntura: efeitos sobre a inflamação e o estresse oxidativo induzidos por gentamicina no testículo em ratos wistar - Guimarães, André Brito Bastos (2022)
The gonads, fundamental organs for animal reproduction, exhibit low levels of antioxidant defenses and require a large amount of energy to perform their function. Gentamicin (GM) can promote increased concentrations of reactive oxygen species, resulting in oxidative stress. Curcuma is the rhizome of a herbaceous plant, rich in terpenoids that has antioxidant and anti-inflammatory activities. Electroacupuncture (EAc) is a neuromodulatory therapeutic modality that uses small electrical stimuli applied to two or more needles inserted into acupuncture points. To evaluate the antioxidant and anti-inflammatory activity of turmeric (CCM) and EAc, a prospective, controlled and comparative study was carried out in Wistar rats subjected to the toxic effects of GM. Fifty-six male rats, with an average weight of 156.8 g. were randomly distributed into seven groups: G1–Saline Control, G2- Diluent Control G3-CCM 100mg, G4-CCM 200mg, G5-EAc100 (Electroacupuncture 100 Hz), G6 – CCM 100mg+EAc 100Hz and G7-CCM 200mg+EAC. All animals received GM (100mg/Kg i.p.) for 5 consecutive days. From the 7th day, the rats were treated with CCM and EAc on alternate days, for 12 days. Arterial blood samples and testes were collected 48 hours after the end of the experiment, under anesthesia with ketamine+xylazine i.p. Biochemical parameters analyzed included glucose, urea, creatinine, nitrites (NO2), thiobarbituric acid reactive substances (TBARS), reduced glutathione (GSH) and myeloperoxidase (MPO).There was a significant increase in NO2 concentrations in the testis, an increase in plasma and testis GSH and a decrease in TBARS concentrations in the plasma and testis, in addition to a decrease in MPO activity in the testis.It is concluded that the use of turmeric alone or associated with EAc 100 Hz has a protective effect on testicular damage induced by high doses of GM, demonstrated by the significant increase in GSH concentrations, reduction in TBARS concentrations and MPO activity. Testicular oxidative damage was confirmed by increased NO2.